Avances del Observatorio de Educación Médica y Derechos Humanos - Vázquez-Martínez, Francisco Domingo; Gutiérrez-Aguilar, Pedro; Saiz-Calderón Gómez, Manuel; Luzanía-Valerio, Manuel Salvador (UVserva, 2021)
Se observa que la razón que dio origen a la fundación del Observatorio de Educación Médica y Derechos Humanos (OBEME) sigue presente: la Comisión Nacional de Derechos Humanos sigue realizando recomendaciones a las instituciones de salud originadas en violaciones a los derechos de pacientes atendidos por estudiantes de medicina no supervisados. El observatorio ha realizado dos informes (2017-2018 y 2018-2019) en los que se observan grandes áreas de oportunidad para mejorar la supervisión de los estudiantes de medicina de la Universidad Veracruzana (UV). Para aprovecharlas, se presenta el diplomado de “Educación médica y derechos humanos”, mismo que se realizará con el apoyo de las autoridades universitarias y participación de las cinco facultades de Medicina de la UV. Advances from the Medical Education and Human Rights Observatory Abstract: It is observed that the reason that gave rise to the foundation of the Medical Education and Human Rights Observatory (OBEME) is still present: the National Human Rights Commission continues to make recommendations to health institutions originating from violations of the rights of patients attended by unsupervised medicine students. The observatory has produced two reports (2017-2018 and 2018-2019) in which large areas of opportunity are observed to improve the supervision of medical students at the Universidad Veracruzana (UV). To take advantage of them, the diploma on "Medical education and human rights" is presented, which will be carried out with the support of the university authorities and the participation of the five UV medical schools. Keywords: medical education; education rights; clinical supervision.